RETRACTED: HIF-1α Affects the Neural Stem Cell Differentiation of Human Induced Pluripotent Stem Cells via MFN2-Mediated Wnt/β-Catenin Signaling - Cui, Peng; Zhang, Ping; Yuan, Lin; Wang, Li; Guo, Xin; Cui, Guanghui; Zhang, Yanmin; Li, Minghua; Zhang, Xiaowei; Li, Xiaoqiang; Yin, Yuxin; Yu, Zhendong (Frontiers in Cell and Developmental Biology, 2021)
ABSTRACT Hypoxia-inducible factor 1α (HIF-1α) plays pivotal roles in maintaining pluripotency, and the developmental potential of pluripotent stem cells (PSCs). However, the mechanisms underlying HIF-1α regulation of neural stem cell (NSC) differentiation of human induced pluripotent stem cells (hiPSCs) remains unclear. In this study, we demonstrated that HIF-1α knockdown significantly inhibits the pluripotency and self-renewal potential of hiPSCs. We further uncovered that the disruption of HIF-1α promotes the NSC differentiation and development potential in vitro and in vivo. Mechanistically, HIF-1α knockdown significantly enhances mitofusin2 (MFN2)-mediated Wnt/β-catenin signaling, and excessive mitochondrial fusion could also promote the NSC differentiation potential of hiPSCs via activating the β-catenin signaling. Additionally, MFN2 significantly reverses the effects of HIF-1α overexpression on the NSC differentiation potential and β-catenin activity of hiPSCs. Furthermore, Wnt/β-catenin signaling inhibition could also reverse the effects of HIF-1α knockdown on the NSC differentiation potential of hiPSCs. This study provided a novel strategy for improving the directed differentiation efficiency of functional NSCs. These findings are important for the development of potential clinical interventions for neurological diseases caused by metabolic disorders.